2017
DOI: 10.1002/bip.23022
|View full text |Cite
|
Sign up to set email alerts
|

Modeling interactions between a β‐O‐4 type lignin model compound and 1‐allyl‐3‐methylimidazolium chloride ionic liquid

Abstract: Aiming at understanding the molecular mechanism of the lignin dissolution in imidazolium-based ionic liquids (ILs), this work presents a combined quantum chemistry (QC) calculation and molecular dynamics (MD) simulation study on the interaction of the lignin model compound, veratrylglycerol-β-guaiacyl ether (VG) with 1-allyl-3-methylimidazolium chloride ([Amim]Cl). The monomer of VG is shown to feature a strong intramolecular hydrogen bond, and its dimer is indicated to present important π-π stacking and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…Two approaches for ionic liquid deconstruction have been investigated. Initially, there was a focus on cellulose dissolving ionic liquids, most prominently 1‐ethyl‐3‐methylimidazolium acetate, [EMIM][OAc] . More recently, a subclass of ionic liquids was discovered that has a high activity for separating cellulose and lignin but do not dissolve cellulose .…”
Section: Introductionmentioning
confidence: 99%
“…Two approaches for ionic liquid deconstruction have been investigated. Initially, there was a focus on cellulose dissolving ionic liquids, most prominently 1‐ethyl‐3‐methylimidazolium acetate, [EMIM][OAc] . More recently, a subclass of ionic liquids was discovered that has a high activity for separating cellulose and lignin but do not dissolve cellulose .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the wettability of the drug increased from the H-bond between the alkalizers and Kollidon ® VA64. These results show that the intermolecular interaction in SD systems is important for improving the solubility and dissolution of GA [68]. The in vitro dissolution test was performed for API (pure), BSD, LA-TSD, and MG-TSD in HCl (pH 1.2), pH 4.5, pH 6.8, and pH 7.4 buffers.…”
Section: Solubility and Dissolution Of Optimal Formulationmentioning
confidence: 93%
“…This stronger intermolecular interaction destroys the stable crystal structure of GA, which is the inherent reason for the increased solubility of GA. Similarly, the binding energy of the GA-MG ion pair is lower than that of the GA-LA ion pair, and the hydrogen bond of the MG-VA extrudate is stronger than that of LA extrudate [68]. This explains why the dissolution of MG-TSD is higher than that of LA-TSD.…”
Section: Molecular Dockingmentioning
confidence: 98%
See 1 more Smart Citation
“…(2017) 7 and Ji et al (2012) 28 performed QC calculations on ILlignin systems and deduced that stronger H-bonding interactions between lignin and imidazolium-based IL mixtures drive lignin dissolution. Further, Zhu et al (2017) studied the dissolution behavior of lignin (veratrylglycerol-β-guaiacyl ether) in 1-allyl-3-methylimidazolium chloride ([Amim]Cl) by both QC and molecular dynamics (MD) simulations 29 and showed that chloride anions form strong hydrogen bonds with lignin, while the cation [Amim] + interacts with lignin via weaker π-π stacking and van der Waals interactions. In the literature, imidazolium-based cations are the most studied ILs for lignin dissolution by both computational and experimental.…”
Section: Introductionmentioning
confidence: 99%